Young people who experience acute emotional rewards of alcohol more likely to become problem drinkers. Issue 8 (5th July 2021) - Knopf, Alison
Abstract : A study has found that young people who experience acute emotional rewards from drinking — either because of increased pleasure or decreased lack of pleasure — are more likely to develop problem drinking in short order than those who do not experience these rewards.